Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Solve for [tex]\( x \)[/tex]:

[tex]\[ \left|\begin{array}{rrr}x & -1 & 2 \\ 2x & 1 & -3 \\ 3 & -4 & 5\end{array}\right| = 29 \][/tex]


Sagot :

To solve the problem:

[tex]\[ \left|\begin{array}{rrr} x & -1 & 2 \\ 2x & 1 & -3 \\ 3 & -4 & 5 \end{array}\right| = 29 \][/tex]

we need to calculate the determinant of the matrix and solve for [tex]\( x \)[/tex] when the determinant equals 29. Here is the step-by-step solution:

1. Define the Matrix:

[tex]\[ A = \begin{pmatrix} x & -1 & 2 \\ 2x & 1 & -3 \\ 3 & -4 & 5 \end{pmatrix} \][/tex]

2. Calculate the Determinant:

The determinant of a 3x3 matrix can be computed using the general formula:
[tex]\[ \text{det}(A) = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]
where
[tex]\[ A = \begin{pmatrix} a & b & c \\ d & e & f \\ g & h & i \end{pmatrix} \][/tex]

For our matrix [tex]\( A \)[/tex]:
[tex]\[ a = x, \quad b = -1, \quad c = 2 \][/tex]
[tex]\[ d = 2x, \quad e = 1, \quad f = -3 \][/tex]
[tex]\[ g = 3, \quad h = -4, \quad i = 5 \][/tex]

Plug these values into the determinant formula:

[tex]\[ \text{det}(A) = x \left(1 \cdot 5 - (-3) \cdot (-4)\right) - (-1) \left(2x \cdot 5 - (-3) \cdot 3\right) + 2 \left(2x \cdot (-4) - 1 \cdot 3\right) \][/tex]

Simplify each term:
[tex]\[ = x (5 - 12) + (2x \cdot 5 + 9) + 2 (-8x - 3) = x (-7) + (10x + 9) + 2 (-8x - 3) = -7x + 10x + 9 - 16x - 6 = -7x + 10x - 16x + 9 - 6 = -13x + 3 \][/tex]

So the determinant of the matrix is:
[tex]\[ \text{det}(A) = 3 - 13x \][/tex]

3. Set the Determinant Equal to 29 and Solve for [tex]\( x \)[/tex]:

[tex]\[ 3 - 13x = 29 \][/tex]

Solve the equation for [tex]\( x \)[/tex]:
[tex]\[ -13x = 29 - 3 \][/tex]
[tex]\[ -13x = 26 \][/tex]
[tex]\[ x = \frac{26}{-13} \][/tex]
[tex]\[ x = -2 \][/tex]

Thus, the value of [tex]\( x \)[/tex] that satisfies the determinant equation is:

[tex]\[ x = -2 \][/tex]


So the determinant of the matrix is [tex]\( 3 - 13x \)[/tex], and the solution to the equation when the determinant equals 29 is [tex]\( x = -2 \)[/tex].